Genetic inhibition of PKCε attenuates neurodegeneration after global cerebral ischemia in male mice. Issue 4 (29th November 2018) - Kumar, Varun; Weng, Yi‐Chinn; Wu, Yu‐Chieh; Huang, Yu‐Ting; Liu, Tung‐Hsia; Kristian, Tibor; Liu, Yu‐Li; Tsou, Hsiao‐Hui; Chou, Wen‐Hai
Abstract: Global cerebral ischemia that accompanies cardiac arrest is a major cause of morbidity and mortality. Protein Kinase C epsilon (PKCε) is a member of the novel PKC subfamily and plays a vital role in ischemic preconditioning. Pharmacological activation of PKCε before cerebral ischemia confers neuroprotection. The role of endogenous PKCε after cerebral ischemia remains elusive. Here we used male PKCε‐null mice to assess the effects of PKCε deficiency on neurodegeneration after transient global cerebral ischemia (tGCI). We found that the cerebral vasculature, blood flow, and the expression of other PKC isozymes were not altered in the PKCε‐null mice. Spatial learning and memory was impaired after tGCI, but the impairment was attenuated in male PKCε‐null mice as compared to male wild‐type controls. A significant reduction in Fluoro‐Jade C labeling and mitochondrial release of cytochrome C in the hippocampus was found in male PKCε‐null mice after tGCI. Male PKCε‐null mice expressed increased levels of PKCδ in the mitochondria, which may prevent the translocation of PKCδ from the cytosol to the mitochondria after tGCI. Our results demonstrate the neuroprotective effects of PKCε deficiency on neurodegeneration after tGCI, and suggest that reduced mitochondrial translocation of PKCδ may contribute to the neuroprotective action in male PKCε‐null mice. Abstract : Neural cell death after transient global cerebral ischemia (tGCI) was attenuated in the hippocampus of mice lacking PKCε. Representative images of cresyl violet‐stained brain slices from Prkce +/+ and Prkce −/− mice 3 days after tGCI. Arrowheads indicate degenerative neurons with pyknotic and shrunken nuclei in the enlarged CA1 region of a Prkce +/+ brain slice (lower panels).